2018
DOI: 10.1111/cns.12801
|View full text |Cite
|
Sign up to set email alerts
|

Nafamostat mesilate attenuates inflammation and apoptosis and promotes locomotor recovery after spinal cord injury

Abstract: Upon NM treatment, the functional and histological outcomes were improved, and microenvironment upon SCI was modulated. As a clinically approved drug, NM holds promise for clinical use after spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…BBB score was used to evaluate the recovery of motor function in rats after SCI . Each rat was evaluated and recorded weekly from 1 to 8 weeks after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…BBB score was used to evaluate the recovery of motor function in rats after SCI . Each rat was evaluated and recorded weekly from 1 to 8 weeks after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Together, primary and secondary injuries lead to irreversible neuronal damage, which ultimately culminates in poor functional recovery of patients following SCI [9]. Thus, preventing irreversible damage by targeting pathways of programmed cell death such as apoptosis, pyroptosis, and autophagy may be a promising strategy for treating SCI [10][11][12].…”
Section: Ivyspringmentioning
confidence: 99%
“…Sildenafil citrate, a phosphodiesterase inhibitor, was found to exert a neuroprotective effect on the spinal cord after ischemia/reperfusion injury by attenuating inflammatory mediators [ 19 ]. Our team’s previous study showed that a synthetic serine protease inhibitor, nafamostat mesylate, could attenuate inflammation and apoptosis and promote locomotor recovery after SCI [ 20 ]. Other biological events play an early protective role, such as the defense response caused by the response to stress.…”
Section: Discussionmentioning
confidence: 99%